Genetical, Morphological, Behavioral, and Ecological Traits Support the Existence of Three Brazilian Species of the Anastrepha fraterculus Complex of Cryptic Species - Selivon, Denise; Perondini, André Luiz P.; Hernández-Ortiz, Vicente; doVal, Francisca Carolina; Camacho, Agustin; Gomes, Fernando R.; Prezotto, Leandro F. (Frontiers in Ecology and Evolution, 2022)
Within the Neotropical genus Anastrepha, the nominal species Anastrepha fraterculus is widely distributed from Mexico through northern Argentina. Currently it comprises a complex of at least eight cryptic species—known as the Anastrepha fraterculus complex (AF complex)—three of which occur in Brazil: A. sp1 aff. fraterculus, A. sp.2 aff. fraterculus, and A. sp.3 aff. fraterculus. In this study, we present the results of a broad integrated analysis of multiple biological attributes in samples of the three species collected in sympatric areas. Analyses of the mitotic chromosomes confirm that all of them differ in sex chromosomes, and that the relative frequency of the distinct karyotypes is associated with variation of altitude. In these sympatric areas, a single female hybrid karyotype was detected within a significant sample of individuals. Population samples were analyzed for the ribosomal transcribed spacer ITS1, confirming that the three species have specific sequence types. Observations of reproductive behavior under laboratory conditions revealed that A. sp.1 and A. sp.2 mate early in the morning, while A. sp.3 mates in the middle of the day. A bimodal distribution of mating time was observed for hybrids in the laboratory, obtained between A. sp.1 and A. sp.3. In a mating choice experiment, most of the mating pairs were homospecific. In addition, through a list of the most frequent hosts associated with the geographical occurrence, a bioclimatic model of their potential distribution was generated. Morphometric analyses of wings clearly demonstrated differences among the three species, for both males and females. Based on a wing image of the A. fraterculus (Wiedemann 1830) holotype, the morphometric analysis indicated that the holotype would correspond to a male of A. sp.2 aff. fraterculus. The information provided by this report is not only useful for taxonomic purposes, but also reveals aspects to be considered in any reconstruction of an evolutionary scenario of the Anastrepha fraterculus complex.